2021
DOI: 10.1115/1.4050336
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Additive Manufacturing on Internal Cooling Channels With Varying Diameters and Build Directions

Abstract: The use of additive manufacturing (AM) processes, such as direct metal laser sintering, provides the design freedom required to incorporate complex cooling schemes in gas turbine components. Additively manufactured turbine components have a range of cooling feature sizes and, because of the inherent three-dimensionality, a wide range of build angles. Previous studies have shown that AM build directions influence internal channel surface roughness that, in turn, augment heat transfer and pressure loss. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 14 publications
2
13
0
3
Order By: Relevance
“…Gradl et al (2021) extensively reported on the part-to-part variation of different geometries including thin walls, holes, hollow and protruding cylinders. Relative geometric error decreased with increasing feature size, which is similar to results for circular channels from Wildgoose et al (2021). Regardless of the part geometry, all components from Gradl et al (2021) contained deviations from their design intent.…”
Section: Causes For Geometric Variation Of Additively Manufactured Co...supporting
confidence: 70%
See 3 more Smart Citations
“…Gradl et al (2021) extensively reported on the part-to-part variation of different geometries including thin walls, holes, hollow and protruding cylinders. Relative geometric error decreased with increasing feature size, which is similar to results for circular channels from Wildgoose et al (2021). Regardless of the part geometry, all components from Gradl et al (2021) contained deviations from their design intent.…”
Section: Causes For Geometric Variation Of Additively Manufactured Co...supporting
confidence: 70%
“…Similar to the film-cooling hole, the angle at which the channel is relative to the build plate impacts the resulting tolerances and geometry. Snyder et al (2015), Mingear et al (et al2019), Wildgoose et al (2021), Kamat and Pei (2019), and Kasperovich et al (2021) showed that cooling channels built perpendicular to the build plate result in the lowest surface roughness and deviation from design intent. Wildgoose et al (2021) showed that for a circular channel fabricated at different build directions, the standard deviation in hydraulic diameter increases 166% when going from a channel built perpendicular to parallel with the build plate.…”
Section: Progress In Using Am To Manufacture Turbine Cooling Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Product design optimization methods including lattice, topology and variable thickness can be digitally generated and fine-tuned based on design for additive manufacturing (DfAM) rules to suit specific AM subcategory prior physical commitments. Different studies have investigated how optimized structures including honeycombs, lattice, variable thickness, build plan, process parameters (mainly from material deposition, beam shapes or spots) influence functional properties, energy intensities and related costs of high-performance metals [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%